A Review for the Design and Optimization of Catalysts: The Use of Statistics as a Powerful Tool for Literature Analysis - Tatiana Martinez; Laura Stephania Lavado Romero; D. Estefania Rodriguez; Jahaziel Amaya (Chemistry)
In this study, a statistical analysis of results reported in the literature was conducted through a 2n experimental design on the synthesis of bifunctional catalysts used in the production of lighter fuels, aiming for optimization while considering factors such as support (bentonite and vermiculite), acidity modifier (zirconium and cerium), metal (tungsten and molybdenum), metal content (5% and 10%), promoter (nickel and cobalt), and heteropolyacids (tungstophosphoric acid and molybdophosphoric acid), identifying their influence on textural properties and catalytic performance. Regarding the textural properties, vermiculite proved to be the most favorable support due to its high porosity. It was also established that the implemented metals impart positive characteristics to the catalysts due to their various properties; however, incorporating large amounts led to an adverse effect by clogging the pores. Catalytic performance was analyzed in isomerization and cracking reactions, which were enhanced by the use of cerium due to the presence of Brønsted acid sites and molybdenum for its stability. In this way, the statistical analysis conducted in this study was crucial for identifying the influence of key factors on the textural properties and catalytic performance of bifunctional catalysts. Using a 2n experimental design allowed for a systematic evaluation of variables reported in the literature, such as support, acidity modifiers, metals, metal content, promoters, and heteropolyacids.